Em busca do tempo perdido : das crises do Estado e da Constituição à adequação e contribuição do Direito Internacional dos Direitos Humanos para a abertura dos Arquivos da Ditadura Militar Brasileira - Seffrin, Ana Carolina Guimarães (Universidade do Vale do Rio dos Sinos, 2010)
The following study investigates the importance and relevance of the legal problematic analysis regarding the archives from the Brazilian military dictatorship period, 1964/1985, towards the movement of the International Law of Human Rights developing with the end of the Second Great War. Through the historic-critic exposition regarding the dictatorial period in Brazil, is recognized a pragmatic crises present in the State in contemporary times, resulting strongly from the so called anos de chumbo (or lead years), with reference to the importance on the access of information as a fundamental human right and the necessity to respect the Federal Constitution of 1988 and other pacts and relevant international declarations to the matter. The critical approach will be one philosophical following Hannah Arendt and Walter Benjamin observations in which relates the present politic state of obscurity of information regarding the country?s past. Judging the necessity to vouch for the broad public access of information related to the period as a means to the effectual of established constitutional rights. Establishing premises linked to Rights to Truth and Memory, limiting that the State of Exception in Brazil in the military dictatorship must be revised in levels which are social, psychological, historical, cultural and, mainly, legal. Valuing the fundamental problematic core in admitting the necessity of governmental politics of management of public archives secret through international norms of human rights protection, deepen the work of the State before the recognition of the civil and political rights as fundamental pillar to the maintenance of the human being dignity. Approaching the theme of Transitional Justice as response to systematic violations and generalized to human rights, intending recognize the basis of a justice to be adapted and build in societies which develop after periods of generalized violations of the human rights. To conclude, the research is inserted in the Concentration Line of Hermeneutic, Constitution and Concretization of Rights, from the Post-graduation Program of Law from University Vale do Rio dos Sinos - UNISINOS - intending take the issue into a critic reflexion in the fight for the effectuation of rights, in a constitutional and international level, in the apparatus of the Democratic State of Law.
Keywords: Arquivos da ditadura militar brasileira; Direito Internacional dos Direitos Humanos; Concretização de direitos; Crise paradigmática; Estado Democrático de Direito; Justiça de transição; Direito Público; Dictatorship military archives; International Law of the Human Rights; Concretization of rights; Pragmatic crises; Democratic State of Law; Transition justice; Public law; ACCNPQ::Ciências Sociais Aplicadas::Direito